Relative Value and Customer Choice in Loan Decisions: An Application of the Wallet Allocation Rule. (May 2016) - Aksoy, Lerzan; Keiningham, Timothy L.; Buoye, Alexander; Ball, Joan
Abstract: Purpose – This research applies the Wallet Allocation Rule (WAR) to provide marketing scholars and practitioners with a deeper understanding of the key drivers of loan selection and to estimate the relative value borrowers place on various attributes when selecting a loan provider among competitors. Design/methodology/approach – A survey of 642 credit union (CU) members from nine geographically dispersed USA CUs was conducted. WAR analysis was conducted to measure the relative value customers place on the selected variables within and across the financial institutions that were part of the borrowers' consideration sets. Findings – WAR analysis revealed stark differences in the value of factors in the selection of a bank or a credit union for first mortgages, suggesting that WAR analysis is a useful tool for understanding the relative value of various attributes in the selection of one loan provider over another. Originality/value –This research provides a significant contribution to both the service literature and the scientific literature in general by providing a user-friendly and scientifically tested analysis tool to measure relative value distances of ranked data and providing additional evidence for the usefulness of WAR analysis to better understand relative customer satisfaction and its implications for consumer behavior and service marketing.